The ACTN3 R577X polymorphism in Russian endurance athletes - Ahmetov, I. I.; Druzhevskaya, A. M.; Astratenkova, I. V.; Popov, D. V.; Vinogradova, O. L.; Rogozkin, V. A. (British Journal of Sports Medicine, 2010)
Objective: The functional 577R allele of the alpha-actinin-3 (ACTN3) gene has been reported to be associated with elite power athlete status, while the nonfunctional 577XX genotype (predicts an alpha-actinin-3 deficient phenotype) has been hypothesised as providing some sort of advantage for endurance athletes. In the present study, the distribution of ACTN3 genotypes and alleles in Russian endurance-oriented athletes were examined and association between ACTN3 genotypes and the competition results of rowers were sought.